A Comparison of Rural Educational Disadvantage in Australia, Canada, and New Zealand Using OECD's PISA. (October 2018) - Sullivan, Kevin; McConney, Andrew; Perry, Laura B.
This study compares rural educational disadvantage across Australia, Canada, and New Zealand using data from the Organisation for Economic Co-operation and Development's Programme for International Student Assessment (PISA). Across the three countries, student reading literacy and school learning environments are less positive in rural communities than in urban. Furthermore, rural disadvantage in educational outcomes (reading) and opportunities is greater in Australia than Canada or New Zealand. This could be seen as surprising as student socioeconomic status (SES), typically a strong predictor of educational outcomes, is similar for rural communities in Australia and Canada, but lower in New Zealand. Rural school principals in Australia are most likely among the three countries to report that shortages of teaching personnel hinder learning. This could suggest that policies and structures can play a role in ameliorating or exacerbating rural educational disadvantage. We conclude with questions and recommendations for future research.